Novel catalytic micromotor of porous zeolitic imidazolate framework-67 for precise drug delivery. Issue 24 (7th June 2018) - Wang, Linlin; Zhu, Hongli; Shi, Ying; Ge, You; Feng, Xiaomiao; Liu, Ruiqing; Li, Yi; Ma, Yanwen; Wang, Lianhui
Abstract : Novel catalytic micromotors based on porous ZIF-67 were used as efficient fluorescence drug (DOX) carriers. Benefiting from the porous nature and high surface area, these micromotors display effective motion, long durable movement life and high drug loading capacity. Abstract : Micromotors hold promise as drug carriers for targeted drug delivery owing to the characteristics of self-propulsion and directional navigation. However, several defects still exist, including high cost, short movement life, low drug loading and slow release rate. Herein, a novel catalytic micromotor based on porous zeolitic imidazolate framework-67 (ZIF-67) synthesized by a greatly simplified wet chemical method assisted with ultrasonication is described as an efficient anticancer drug carrier. These porous micromotors display effective autonomous motion in hydrogen peroxide and long durable movement life of up to 90 min. Moreover, the multifunctional micromotor ZIF-67/Fe3 O4 /DOX exhibits excellent performance in precise drug delivery under external magnetic field with high drug loading capacity of fluorescent anticancer drug DOX up to 682 μg mg −1 owing to its porous nature, high surface area and rapid drug release based on dual stimulus of catalytic reaction and solvent effects. Therefore, these porous ZIF-67-based catalytic micromotors combine the domains of metal–organic frameworks (MOFs) and micomotors, thus developing potential resources for micromotors and holding great potential as label-free and precisely controlled high-quality candidates of drug delivery systems for biomedical applications.